SARS-COV2 Virus in Tears and Conjunctival Secretions of COVID-19 Patients: Doi: 10.36351/pjo.v37i3.1222 - Gull, Ambreen; saleem, M.Rafaaq; Niazi, Fuad Ahmad Khan (Pakistan Journal of Ophthalmology, 2021)
Purpose: To determine the presence of SARS-COV 2 viruses in tears and conjunctival secretions of patients with diagnosed COVID-19. Study Design: Prospective interventional case series. Place and Duration of Study: Rawalpindi Institute of Urology, Department of infectious diseases, Holy Family Hospital, Rawalpindi Medical University, from September 2020 to October 2020. Methods: Samples of conjunctival and tear secretions were collected from 60 hospitalized patients of COVID-19 who were confirmed with nasopharyngeal swabs test. Disposable conjunctival swab sticks were used for sampling. Samples were taken within 3 days of admission. SARS-COV 2 virus evaluation in tears and conjunctival secretions was done by Qualitative RT-PCR (Reverse transcriptase polymerase chain reaction) analysis. Ocular features were documented. Regarding systemic course of illness, details were noted from their hospital records. Results: Mean age of the patients was 56.63 ± 16.373 years. Out of 60 patients, 42 were males and 18 were females. Twenty two (36.6%) patients had mild disease and moderate and severe disease was present in 19 patients (31.6%) each. Six (10%) patients had positive conjunctival and tear secretions for SARS-COV 2 viral RNA. All patients with positive ocular secretions for viral RNA were in first week of course of disease and 3 patients had severe COVID 19 disease signifying high viral load. Only one patient had conjunctivitis and ocular symptoms of redness and foreign body sensation. Conclusion: There is likelihood of SARS-COV 2 virus transmission via ocular secretions as frequency of patients with SARS-COV 2 viral RNA detected in tears was 10% in current study therapeutic services. Key Words: SARS-COV 2 Virus, COVID 19, Conjunctivitis, Qualitative RT-PCR, Ocular Manifestations